The relationship between Financial Management Practices, Operational Efficiency and Organizational Performance in the Service sector of Pakistan - Anwar Hussain Noorani; Faiz Ali; Sayeed Sabir; Muhammad Ilyas (Indus Journal of Social Sciences, 2025)
Purpose – This study tries to study the position of operational performance as a mediator within the dating between organizational overall performance and economic control practices. Design/methodology/approach – Data from 100 participants across 15 Banking Sector institutions in the Baltistan Region of Gilgit-Baltistan, Pakistan, were analyzed. The dimensions and validity of the research variables were assessed by regression analysis. Findings – The results recommend that monetary management Practices are vital for the prediction of Organizational performance. The relationship between organizational success and financial management methods is improved by operational efficiency. Research limitations/implications – The data were limited to a cross-sectional design in the Baltistan context, which may render it less appropriate for generalization throughout Pakistan. moreover, the pattern length is particularly smaller; but, the effects aren’t adversely affected. Originality/value – The significance and distinctiveness of this study are derived from the current absence of research in Pakistan regarding the role of Financial Management Practices in improving Operational Efficiency. In this investigation, the impact of operational efficiency on the correlation between organizational performance and financial management practices is extensively investigated.